Assessing Factors Associated With Altmetric Attention Score: A Preliminary Study of 3 Hand Surgery Journals. (November 2022) - Bernstein, David N.; Richardson, Michelle A.; Hammert, Warren C.
Background: Traditional measures of evaluating scholarly output do not capture the impact social media can provide in disseminating and promoting research. We sought to better understand the level of online attention that high-quality hand research received. Methods: Scientific manuscripts published from 2017 in Journal of Hand Surgery (American Volume) ( JHS-A ), Journal of Hand Surgery ( European Volume ) ( JHS-E ), and HAND were recorded. Manuscript characteristics were determined, including the number of citations. Altmetric Attention Score (AAS), a measure of a manuscript's online attention and impact, was determined, as well as Twitter mentions, Facebook mentions, and news outlet mentions. Spearman rho (ρ) correlation coefficient was used to evaluate the relationship between the number of citations and AAS. Multivariable linear regression analysis was performed to determine which manuscript factors were associated with AAS. Results: A total of 323 manuscripts were identified. There was a weak positive correlation between the number of citations and AAS; however, this relationship did not exist for each individual journal. Publication in HAND and JHS-E were associated with lower average manuscript AAS when using JHS-A as the reference group. Two additional factors were also associated with increased manuscript AAS: (1) being a clinical study focused on a specific upper extremity anatomical location; and (2) increasing number of institutions on a study. Conclusions: Publication in HAND and JHS-E were associated with lower manuscript AAS when using JHS-A as the reference group, suggesting that HAND and JHS-E have room for improvement in using social media to share their high-quality hand surgery scientific articles.